Teaching Cooking Skills to Young Women with Mild Intellectual Disability: The Effectiveness of Internet Websites - Hanadi Hussein Alqahtani; Naomi A. Schoenfeld (Arizona State University, 2014)
The purpose of this preliminary study was to evaluate the effectiveness of using streaming video websites to improve, maintain, and generalize the cooking (meal-making) skills of four young women (18-22 years old) diagnosed with intellectual disabilities. A pre-experimental design was used to evaluate the effectiveness of a web-based multimedia program. Instruction consisted of supported viewing and imitation of cooking videos available online, with students searching for a video of the desired recipe, viewing it, and then imitating the video's sequence of steps to complete the cooking task. Results were assessed by means of a questionnaire administered to each participant's primary caregivers, and indicated that the structured use of the websites was effective in improving students' meal-making skills. Implications and suggestions for future research are also discussed.